Tulsian’s Cost & Management Accounting for CA Intermediate Course (Group I) Tulsian’s Quick Revision for Cost & Management Accounting for CA Intermediate Course (Group I) - Tulsian, P. C.; Tulsian, Tushar;Tulsian, Bharat (S. Chand Noida, 2023)
"TULSIAN'S COST & MANAGEMENT ACCOUNTING FOR CA INTERMEDIATE COURSE (GROUP I) The book has been designed for the students of CA Intermediate course (Group I) for the subject Cost and Management Accounting (Paper 3) as per the syllabus issued by the Institute of Chartered Accountants of India. It serves as a self-study text and provides an overview and essential guidance for understanding complex accounting principles and practices. It includes detail discussion on cost and management accounting, cost ascertainment, methods of costing and cost control analysis including standard costing, marginal costing and budget with budgetary control. The book has been written in simple and lucid manner covering all important equations, formulae, figures and practical steps in a systematic manner to aid students learning. Based on the author's proven approach teach yourself style, the book is replete with numerous illustrations, exhibits and easy retention of concepts. QUICK REVISION FOR COST & MANAGEMENT ACCOUNTING - CA INTERMEDIATE COURSE (GROUP I) This book is a companion to Tulsian's Cost and Management Accounting for CA Intermediate Course (Group I). It provides a quick revision of the concepts discussed in the main textbook and helps students to test their knowledge. The book helps in making the revision process easy by providing candidates with fully solved scanner, model test papers with solutions and CA Intermediate examination papers for practice. The content is exam-oriented, highly relevant and focuses on the important topics appearing in the exam."